Effects of Home-Based Baduanjin Exercise on Left Ventricular Remodeling in Patients With Acute Anterior ST-Segment Elevation Myocardial Infarction: Study Protocol for a Randomized Controlled Trial - Cai, Yinhe; Kang, Liang; Li, Haiyi; Luo, Yuan; Wen, Junmao; Gong, Zhaohui; Chu, Qingmin; Qiu, Yijun; Luo, Chuanjin; Chen, Keyu; Zhao, Xinjun; Li, Rong (Frontiers in Cardiovascular Medicine, 2022)
Background: Left ventricular (LV) remodeling after ST-segment elevation myocardial infarction (STEMI) is the major pathological basis associated with heart failure and increased mortality. Exercise-based cardiac rehabilitation has been verified to significantly improve prognosis and quality of life. As a traditional Chinese Qigong, Baduanjin exercise has effectively alleviated adverse LV remodeling in STEMI patients. Despite this, participation in exercise rehabilitation remains low, and home-based exercise rehabilitation may be an alternative approach. Besides, anterior STEMI is reported to have higher risk of adverse LV remodeling. However, the efficiency regarding home-based Baduanjin exercise on LV remodeling in anterior STEMI patients remains uncertain currently. Methods/design: A single-blind, randomized controlled clinical trial will be conducted to explore the efficacy and safety of home-based Baduanjin exercise in anterior STEMI patients compared with moderate intensity aerobic walking. A total of 114 participants will be assigned randomly to the Baduanjin group or walking control group at a 1:1 ratio. Eligible participants will practice Baduanjin or walking exercise (5 times a week) for 12 weeks, and then followed up for another 12 weeks. The primary outcome is relative change in LV end-diastolic volume. The secondary outcomes include the plasma levels of hypersensitive C-reactive protein and interleukin 6, health-related quality of life measured by EQ-5D-5L, LV ejection fraction, patient health questionnaire-9, generalized anxiety disorder screener-7, short physical performance battery score, and clinical endpoint events. The proportion of circulating regulatory T-cells will be also assessed. Adverse events will be recorded throughout the trial for safety evaluation. Data will be analyzed by researchers blinded to the treatment allocation. Discussion: This study will provide powerful evidence for the use of home-based Baduanjin exercise in anterior STEMI patients in alleviating LV remodeling and improving clinical outcomes. Trial registration: The Research Ethics Committee of the First Affiliated Hospital of Guangzhou University of Chinese Medicine has approved this study (ZYYECK【2020】045). Written informed consent of patients will be required. This trial is registered in the Chinese Clinical Trial Registry (ChiCTR2100047298). Dissemination: Our results will be published in peer-reviewed journals and disseminated through academic conferences and the Internet.